(untitled) (Conferencea, 2022)
Our purpose is to observe how researchers from various scientific backgrounds position themselves in relation to this issue. It is not a question of arguing in favor of a vision of sociolinguistics but of seeing how the authors thematize this question in their disciplinary field(s).In the lines that follow, we will focus on the main themes that run through all the contributions, namely the definitions of sociolinguistics proposed by the authors, the reflections on the debate between internal and external linguistics, the advantages and the limits methods of interdisciplinarity and, finally, the possible "zones of silence" appearing in the interdisciplinary network within which sociolinguistics fits.